At the Mind's Limits : Contemplations by a Survivor on Auschwitz and Its Realities - Amery, Jean (Book collections on Project MUSE., 1980)
""These are pages that one reads with almost physical pain ... all the way to its stoic conclusion.""--Primo Levi""The testimony of a profoundly serious man ... In its every turn and crease, it bears the marks of the true.""--Irving Howe, New Republic""This remarkable memoir ... is the autobiography of an extraordinarily acute conscience. With the ear of a poet and the eye of a novelist, Amery vividly communicates the wonder of a philosopher-a wonder here aroused by the 'dark riddle' of the Nazi regime and its systematic sadism.""--Jim Miller, Newsweek""Whoever has succumbed to torture can no long